2022
DOI: 10.3390/ani12172195
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel Lymph Node Biopsy Is Feasible in Dogs with Scars from Prior Local Excision of Solid Malignancies

Abstract: Sentinel lymph node (SLN) biopsy is a well-established staging tool in canine oncology. This study aims to explore the feasibility of SLN biopsy in dogs with scars from prior excised solid malignancies that were referred for further tumor staging and/or adjuvant treatment options. Mapping was either performed using radiopharmaceutical, methylene blue, and/or near-infrared fluorescent (NIRF) imaging. Thirty-three dogs with 34 scars from prior excision of the mast cell tumor (MCT) (n = 29), soft tissue sarcoma (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…contrast-enhanced ultrasound (CEUS) [32], single-photon emission computed tomography (SPECT) [33], positron emission tomography (PET) [34], pre-and intraoperative lymphoscintigraphy, and the injection of blue dyes for direct visualization or fluorescent dyes for near-infrared (NIR) fluorescent imaging [35]. Corresponding evaluations of indirect radiographic [36][37][38] and CT lymphography [39][40][41][42], lymphoscintigraphy [15,20,24,[43][44][45][46][47], CEUS [25,48], methylene blue staining [20,24,47], and NIR-lymphography [14,47,[49][50][51] are also available for dogs and, most recently, also for cats [26,52].…”
Section: Sln Mapping In Companion Animalsmentioning
confidence: 99%
See 3 more Smart Citations
“…contrast-enhanced ultrasound (CEUS) [32], single-photon emission computed tomography (SPECT) [33], positron emission tomography (PET) [34], pre-and intraoperative lymphoscintigraphy, and the injection of blue dyes for direct visualization or fluorescent dyes for near-infrared (NIR) fluorescent imaging [35]. Corresponding evaluations of indirect radiographic [36][37][38] and CT lymphography [39][40][41][42], lymphoscintigraphy [15,20,24,[43][44][45][46][47], CEUS [25,48], methylene blue staining [20,24,47], and NIR-lymphography [14,47,[49][50][51] are also available for dogs and, most recently, also for cats [26,52].…”
Section: Sln Mapping In Companion Animalsmentioning
confidence: 99%
“…Lately, several metareviews in human medicine have confirmed NIR imaging using ICG as a reliable mapping technique compared with the gold standard lymphoscintigraphy [35,77]. After NIR SLN mapping in dogs was initially described in experimental studies in dogs and pigs [50], it is now gaining increased interest in veterinary surgical oncology [14,49,52]. Beer et al published a retrospective study on NIR lymphography in dogs with mast cell tumors.…”
Section: Near-infrared Lymphographymentioning
confidence: 99%
See 2 more Smart Citations
“…The advantages of the incorporation of SLN mapping and biopsy have been largely reported in human medicine and include accurate tumor staging and reduced morbidity compared to radical nodal dissection [ 1 , 7 ]. Similarly, in tumor-bearing dogs, a benefit in terms of accuracy in staging has been documented, and morbidity of the procedure is reportedly low, although studies that compare the morbidity of RLN vs. SLN extirpation are currently not available in the veterinary literature [ 1 , 7 , 22 , 23 , 24 ]. Disadvantages of SLN extirpation include the need for dedicated technologies and the learning curve for the mapping procedure, although the incorporation of SLN biopsy seems to be justified by the well-documented impact of correct nodal staging on prognosis and treatment recommendations for various tumor types [ 3 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%